Upaya Peningkatan Kemampuan Perkalian dengan Menggunakan Media Batang Napier di SDN 34/I Muara Bulian - Alisnaini, Ahmad Farhan; Harliyani, Wiwin; Tusakdiah, Halimah; Fiaski, Cici Adila (MASALIQ, 2023)
One of the subjects that most students experience problems and find it difficult to understand the concepts is mathematics. The task of a teacher is not only to transfer knowledge or convey learning knowledge to students in the classroom. The majority of students explained that subjects related to calculations were subjects that were difficult to understand. The purpose of this research was to assist teachers in improving students' abilities by using stem napier media. The Napier rod is a tool that can help find the product of a number. Napier rods can be used by students to assist in calculating multiplication and division operations. This calculation tool is designed to simplify heavy multiplication tasks. This multiplication bar or napier bar prop is used to calculate multiplication of whole numbers.